Incidences and veterinary clinical management of postpartum diseases among domestic cows and does in Klang Valley, Malaysia - Abdullah, Faez Firdaus Jesse; Peter, Innocent Damudu; Lim, Eric Teik Chung; Tukiran, Nuriza; Bitrus, Asinamai Athliamai; Hambali, Idris Umar; Thlama, Bura Paul; Azhar, Nur Amira; Mohd Lila, Mohd Azmi (Nexus Academic Publishers, 2019)
The postpartum period is a time that is characterised by an increased risk of developing parturition related diseases and disorders by the dam. These may affect production in affected animals. Thee objective of this study was to determine the incidences and methods of clinical management of postpartum diseases among farm animals within the Klang Valley in Selangor, Malaysia. Primary data were obtained from a four-year (January 2013 to December 2017) farm record from sixteen (16) cattle and goats mixed farms. Postpartum diseases and disorders made up 3.4% (53/1550) of total diseases and disorders recorded for cows and does. Out of the 53 cases of postpartum diseases and disorders recorded, the followings were observed; metritis (24.5%), vaginal prolapse (22.6%), pyometra (20.8%), retained placenta (15.1%), uterine prolapse (9.4%), endometritis (5.7%) and uterine tears (1.9%). Most of the recorded postpartum cases were seen in cattle (83.0%) than in goat (17.0%) populations. More postpartum diseases and disorders were seen in younger cows (56.8%) as compared to older cows (43.2%). Similarly, more cases were seen in older does (66.6%) as compared to younger does (33.4%). Furthermore, a higher frequency of postpartum diseases was observed in animals during their rst parturition (77.4%) than in animals during their second (17.0%) or third parturition (5.6%). Flunixin meglumine and oxytetracyclines administered via the uterus were frequently used in clinical management of postpartum diseases. However, a detailed and strict follow up of the cases were lacking (52.8%). This study shows that postpartum diseases are quite common in primipara ruminants in the Klang Valley. Although conventional methods of managing postpartum cases in the Klang valley yielded satisfactory outcomes, there is need for compliance on detailed follow up therapy to avoid cases of treatment failures in affected animals.